2013
DOI: 10.3171/2013.4.peds12474
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-guided cordotomy for the treatment of pediatric cancer pain

Abstract: Percutaneous cordotomy using CT guidance has been shown to be a safe and effective means of reducing pain in adults with cancer in 2 large case series. Its effectiveness in pediatric patients, however, has not been reported. Here, the authors present a case of CT-guided percutaneous cordotomy being used effectively for the treatment of unilateral limb pain in a 9-year-old boy suffering from metastatic medulloblastoma. The efficacy and minimally invasive nature of this procedure support its use in selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Cord displacement up to 0.5 cm has been reported historically 21 and also can be observed in recent CT-guided cordotomies. 5,11,12,15 We observed no problems in our subjects due to spinal cord displacement, and the cord in subject 3 had returned to a normal position on MR imaging 2 days later (On-line Fig 2).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Cord displacement up to 0.5 cm has been reported historically 21 and also can be observed in recent CT-guided cordotomies. 5,11,12,15 We observed no problems in our subjects due to spinal cord displacement, and the cord in subject 3 had returned to a normal position on MR imaging 2 days later (On-line Fig 2).…”
Section: Discussionmentioning
confidence: 90%
“…Several groups have performed myelography during the C1-2 puncture, but published images 4,12,14,15 suggested limited redistribution of viscous contrast because the patient cannot be moved. 5 We preferred a separate myelogram injection to plan the trajectory to the spinothalamic tract relative to the skin entry, lateral C1-2 window, and intrathecal spinal cord position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reddy et al [12] showed that percutaneous cordotomy using CT guidance is safe and effective in reducing pain in paediatric patients suffering from metastatic medulloblastoma.…”
Section: Metastatic Cancermentioning
confidence: 99%